Question

# Solve the pair of linear equations, Also find p if p = 2x + 3

Hint:

### find x by eliminating y and find y by substituting x in the equations .

## The correct answer is: x = 2 ; y = 0 ; p = 7

### Ans :- x = 2 ; y = 0 ; p = 7

Explanation :-

Step 1 :- Find x by eliminating y .

Adding eq1 and eq2

Step 2:- substitute x = 2 in eq 1 to get y

Step 3:- calculate P

Given p = 2x + 3

is the solution to the equation and value of p = 7

### Related Questions to study

### Solve: by using substitution method.

### Solve: by using substitution method.

### Solve: 3x + y = 8; 5x + y = 10 by using elimination method.

### Solve: 3x + y = 8; 5x + y = 10 by using elimination method.

### Solve and by using elimination method.

### Solve and by using elimination method.

### Solve by using elimination method:

### Solve by using elimination method:

### Solve by using elimination method. .

### Solve by using elimination method. .

### Solve the following equation by balancing on both sides: b) 6n+7= 3n+25

### Solve the following equation by balancing on both sides: b) 6n+7= 3n+25

### Solve the following equation by balancing on both sides: a) 5m+9 = 4m + 23

### Solve the following equation by balancing on both sides: a) 5m+9 = 4m + 23

### Solve:

### Solve:

Which of the following could be the *x*-coordinate of a solution to the system of equations above?

**Note: **

If we had to find the y-coordinate of the system of equations, then we put this value of x in the equation to get the value of y. Here, we got a quadratic equation of x, which did not have any term containing x, so it was easier to solve. If the quadratic equation was of the form , then we would use the quadratic formula to solve the equation.

Which of the following could be the *x*-coordinate of a solution to the system of equations above?

**Note: **

If we had to find the y-coordinate of the system of equations, then we put this value of x in the equation to get the value of y. Here, we got a quadratic equation of x, which did not have any term containing x, so it was easier to solve. If the quadratic equation was of the form , then we would use the quadratic formula to solve the equation.

### Solve the equation and check your result 6(3m + 2) – 2(6m – 1) = 3(m – 8) – 6(7m – 6) +9m

### Solve the equation and check your result 6(3m + 2) – 2(6m – 1) = 3(m – 8) – 6(7m – 6) +9m

### Solve and check your answer: 3x – 2(2x – 5) = 2(x + 3) – 8

### Solve and check your answer: 3x – 2(2x – 5) = 2(x + 3) – 8

### Solve: 16 = 4 + 3(x + 2)

### Solve: 16 = 4 + 3(x + 2)

The graph of the function *f *is shown in the *xy*-plane above, where y =f . Which of the following functions could define *f *?

**Note:**

We need to know properties about factors, multiplicity, leading co-efficients and turning points to find out the function from a graph.

The graph of the function *f *is shown in the *xy*-plane above, where y =f . Which of the following functions could define *f *?

**Note:**

We need to know properties about factors, multiplicity, leading co-efficients and turning points to find out the function from a graph.